A novel connexin50 mutation associated with congenital nuclear pulverulent cataracts. Issue 3 (15th November 2007) - Arora, A; Minogue, P J; Liu, X; Addison, P K; Russel-Eggitt, I; Webster, A R; Hunt, D M; Ebihara, L; Beyer, E C; Berthoud, V M; Moore, A T
Abstract : Purpose: To screen for mutations of connexin50 (Cx50)/ GJA8 in a panel of patients with inherited cataract and to determine the cellular and functional consequences of the identified mutation. Methods: All patients in the study underwent a full clinical examination and leucocyte DNA was extracted from venous blood. The GJA8 gene was sequenced directly. Connexin function and cellular trafficking were examined by expression in Xenopus oocytes and HeLa cells. Results: Screening of the GJA8 gene identified a 139 G to A transition that resulted in the replacement of aspartic acid by asparagine (D47N) in the coding region of Cx50. This change co-segregated with cataract among affected members of a family with autosomal dominant nuclear pulverulent cataracts. While pairs of Xenopus oocytes injected with wild type Cx50 RNA formed functional gap junction channels, pairs of oocytes injected with Cx50D47N showed no detectable intercellular conductance. Co-expression of Cx50D47N did not inhibit gap junctional conductance of wild type Cx50. In transiently transfected HeLa cells, wild type Cx50 localised to appositional membranes and within the perinuclear region, but Cx50D47N showed no immunostaining at appositional membranes with immunoreactivity confined to the cytoplasm. Incubation of HeLa cells transfected with Cx50D47N at 27°C resulted in formation of gap junctional plaques. Conclusions: The pulverulent cataracts present in members of this family are associated with a novel GJA8 mutation, Cx50D47N, that acts as a loss-of-function mutation. The consequent decrease in lens intercellular communication and changes associated with intracellular retention of the mutant connexin may contribute to cataract formation.